Fractional Flow Reserve and Instantaneous Wave-Free Ratio as Predictors of the Placebo-Controlled Response to Percutaneous Coronary Intervention in Stable Single-Vessel Coronary Artery Disease: Physiology-Stratified Analysis of ORBITA. Issue 17 (23rd October 2018) - Al-Lamee, Rasha; Howard, James P.; Shun-Shin, Matthew J.; Thompson, David; Dehbi, Hakim-Moulay; Sen, Sayan; Nijjer, Sukhjinder; Petraco, Ricardo; Davies, John; Keeble, Thomas; Tang, Kare; Malik, Iqbal S.; et al.
Abstract : Background: There are no data on how fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) are associated with the placebo-controlled efficacy of percutaneous coronary intervention (PCI) in stable single-vessel coronary artery disease. Methods: We report the association between prerandomization invasive physiology within ORBITA (Objective Randomised Blinded Investigation With Optimal Medical Therapy of Angioplasty in Stable Angina), a placebo-controlled trial of patients who have stable angina with angiographically severe single-vessel coronary disease clinically eligible for PCI. Patients underwent prerandomization research FFR and iFR assessment. The operator was blinded to these values. Assessment of response variables, treadmill exercise time, stress echocardiography score, symptom frequency, and angina severity were performed at prerandomization and blinded follow-up. Effects were calculated by analysis of covariance. The ability of FFR and iFR to predict placebo-controlled changes in response variables was tested by using regression modeling. Results: Invasive physiology data were available in 196 patients (103 PCI and 93 placebo). At prerandomization, the majority had Canadian Cardiovascular Society class II or III symptoms (150/196, 76.5%). Mean FFR and iFR were 0.69±0.16 and 0.76±0.22, respectively; 97% had ≥1 positive ischemia tests. The estimated effect of PCI on between-arm prerandomization-adjusted total exercise time was 20.7 s (95% confidence interval [CI], –4.0 to 45.5; P =0.100) with no interaction of FFR ( P interaction =0.318) or iFR ( P interaction =0.523). PCI improved stress echocardiography score more than placebo (1.07 segment units; 95% CI, 0.70–1.44; P <0.00001). The placebo-controlled effect of PCI on stress echocardiography score increased progressively with decreasing FFR ( P interaction <0.00001) and decreasing iFR ( P interaction <0.00001). PCI did not improve angina frequency score significantly more than placebo (odds ratio, 1.64; 95% CI, 0.96–2.80; P =0.072) with no detectable evidence of interaction with FFR ( P interaction =0.849) or iFR ( P interaction =0.783). However, PCI resulted in more patient-reported freedom from angina than placebo (49.5% versus 31.5%; odds ratio, 2.47; 95% CI, 1.30–4.72; P =0.006) but neither FFR ( P interaction =0.693) nor iFR ( P interaction =0.761) modified this effect. Conclusions: In patients with stable angina and severe single-vessel disease, the blinded effect of PCI was more clearly seen by stress echocardiography score and freedom from angina than change in treadmill exercise time. Moreover, the lower the FFR or iFR, the greater the magnitude of stress echocardiographic improvement caused by PCI. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02062593. Abstract : Supplemental Digital Content is available in the text.